Dynamic root exudate chemistry and microbial substrate preferences drive patterns in rhizosphere microbial community assembly - Zhalnina, Kateryna; Louie, Katherine B.; Hao, Zhao; Mansoori, Nasim; da Rocha, Ulisses Nunes; Shi, Shengjing; Cho, Heejung; Karaoz, Ulas; Loqué, Dominique; Bowen, Benjamin P.; Firestone, Mary K.; Northen, Trent R.; et al. (Nature microbiology, 2018)
Like all higher organisms, plants have evolved in the context of a microbial world, shaping both their evolution and their contemporary ecology. Interactions between plant roots and soil microorganisms are critical for plant fitness in natural environments. Given this co-evolution and the pivotal importance of plant–microbial interactions, it has been hypothesized, and a growing body of literature suggests, that plants may regulate the composition of their rhizosphere to promote the growth of microorganisms that improve plant fitness in a given ecosystem. Here, using a combination of comparative genomics and exometabolomics, we show that pre-programmed developmental processes in plants ( Avena